Factors associated with self-assessment of body weight in women who work out at fitness centers - Porto, Denilson Braga; Azevedo, Bruna Gonçalves De; Melo, Denise Gutierrez De; Christofaro, Diego Giulliano Destro; Codogno, Jamile Sanches; Silva, Camila Buonani Da [UNESP]; Fernandes, Rômulo Araújo [UNESP] (Universidade Federal de Santa Catarina, 2015)
Abstract This study analyzed factors associated with self-assessment of body weight (SABW) among women who engage in physical exercises at fitness centers. Data collection was conducted at the largest fitness centers in the city of Presidente Prudente, SP, Brazil, with a sample of 200 women with a mean age of 25.5±9.7 years. A questionnaire with responses on a Likert scale was used to conduct SABW. Independent variables analyzed were: consulting with a nutritionist, chronological age, nutritional status (by BMI), perceived quality of life and marital status. The chi-square test and binary logistic regression were used for analysis (p<5%). A high proportion of women self-assessed their body weight in categories other than normal (59% [95%CI: 52.2-65.8]), and women with excess weight were more likely to do so (3.70 [95%CI: 1.83-7.49]), as were those with worse perceived quality of life (p=0.001). The women were asked which parts their bodies they wished to change and the abdominal region was the only part that had an association with self-assessment of body weight. There was a high rate of women who self-assessed their body weight in categories other than the option normal and this outcome was associated with worse perceived quality of life and having excess weight. Additionally, the major focus of concern for these women was the abdominal region.

Resumo Analisar os fatores associados à autoavaliação do peso corporal (AAPC) em mulheres praticantes de exercícios físicos em academias. A coleta de dados foi realizada nas maiores academias da cidade de Presidente Prudente-SP, sendo a amostra constituída por 200 mulheres com idade média de 25,5±9,7 anos. A AAPC foi realizada mediante o preenchimento de questionário com opções de resposta em escala de Likert. As variáveis independentes analisadas foram: acompanhamento com nutricionista, idade cronológica, estado nutricional (avaliado pelo IMC), percepção da qualidade de vida e estado civil. O teste qui-quadrado e a regressão logística binária foram utilizados (p<5%). Encontrou-se elevada proporção de mulheres que autoavaliaram seu peso corporal em outras categorias diferentes da opção normal (59% [IC95%: 52,2-65,8]), sendo que as mulheres com excesso de peso apresentaram uma probabilidade maior dessa ocorrência (3,70 [IC95%: 1,83-7,49]), similarmente àquelas com menor percepção da qualidade de vida (p=0,001). Dentre as partes corporais avaliadas, a insatisfação com a região abdominal foi a única que apresentou associação com a autoavaliação do peso corporal. Existe elevada ocorrência de mulheres que autoavaliaram seu peso corporal em outras categorias diferentes da opção normal, as quais estão associadas às piores percepções de qualidade de vida e excesso de peso. Além disso, a região abdominal parece ser um foco central de preocupação nessas mulheres.
Fatores associados à autoavaliação do peso corporal em mulheres praticantes de academia
Keywords: Body image; Fitness centers; Gyms; Quality of life; Women; Academias de ginástica; Imagem corporal; Mulheres; Qualidade de vida